Strategic fertilizer placement in containers influences liverwort (Marchantia polymorpha) growth, reproduction, and competitiveness with ornamentals - Manjot Kaur Sidhu; Sushila Chaudhari; Roberto Lopez; Eric L Patterson; Debalina Saha (Weed Technology)
Liverwort (Marchantia polymorpha L.) is a problematic weed for nurseries and greenhouses, and currently, no effective method exists for controlling it in greenhouses. This study assessed liverwort growth, reproduction, and its competitiveness with ornamental plants in response to the strategic placement of controlled-release fertilizers (CRFs). CRFs were top dressed, incorporated, subdressed, and dibbled on liverwort growth and reproduction. CRFs were subdressed or dibbled at depths of 2.5, 5.1, or 7.6 cm. In each container, the top of the growing medium was inoculated with liverwort gemmae, and the percentage of the container surface covered by liverwort thalli was visually estimated after 2, 4, 6, 8, 10, and 12 wk. At 12wk, gemma cups were counted and after 28 wk, the number of sexual reproductive structures (antheridiophores and archegoniophores) and total fresh biomass of liverwort were recorded. Liverwort growth, gemmae formation, and number of archegoniophores were lowest when CRFs were dibbled or subdressed at depths of 7.6 cm. We also investigated the effects of CRF placement on liverwort competitiveness with a dicot wax begonia (Begonia semperflorens-cultorum L.) and a monocot dracaena (Cordyline indivisa L.). One week after planting the ornamentals and gemmae application, liverwort was thinned to contain 0, 3, or 9 gemmalings per container. The percent increase in growth index of the ornamental plants, and the fresh mass of liverwort and ornamental plants were recorded at the end of the experiment. Results indicated that CRF subdressing and dibbling applied at 7.6 cm were the most effective in reducing liverwort coverage and biomass while improving the growth of both begonia and dracaena. The highest liverwort coverage was measured in containers in which CRF was incorporated. Therefore, strategic fertilizer placement can be an effective method of managing liverwort growth in ornamental container production both in terms of the quality of the ornamentals and their competitiveness with liverwort.